The Integration of Socioscientific Issues-Based Education in Disaster Readiness and Risk Reduction in Enhancing Student Science Achievement - Villarojo, Bryan Paul; Floro, Mercedita (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2024)
This research paper investigates the effects of integrating Socioscientific Issues-Based Education (SSIBE) into formal classroom instruction, specifically within the Disaster Readiness and Risk Reduction (DRRR) course for Grade 11 STEM students. The study employed a quasi-experimental pretest-posttest non-equivalent group design, comparing an experimental group exposed to SSIBE and a control group taught through traditional instruction. Findings revealed that both groups improved their post-test mean percentage scores, with the experimental group achieving mastery-level proficiency. Notably, the experimental group outperformed the control group in post-test scores, indicating the effectiveness of SSIBE in enhancing student science achievement. The integration of socioscientific issues was associated with improved critical thinking, problem-solving skills, and interdisciplinary understanding. Recommendations encompass active student engagement in SSIBE, teacher adoption of innovative methodologies, support from school administrators and government sectors, and avenues for future research exploring long-term impacts and potential challenges of SSIBE implementation.This research paper investigates the effects of integrating Socioscientific Issues-Based Education (SSIBE) into formal classroom instruction, specifically within the Disaster Readiness and Risk Reduction (DRRR) course for Grade 11 STEM students. The study employed a quasi-experimental pretest-posttest non-equivalent group design, comparing an experimental group exposed to SSIBE and a control group taught through traditional instruction. Findings revealed that both groups improved their post-test mean percentage scores, with the experimental group achieving mastery-level proficiency. Notably, the experimental group outperformed the control group in post-test scores, indicating the effectiveness of SSIBE in enhancing student science achievement. The integration of socioscientific issues was associated with improved critical thinking, problem-solving skills, and interdisciplinary understanding. Recommendations encompass active student engagement in SSIBE, teacher adoption of innovative methodologies, support from school administrators and government sectors, and avenues for future research exploring long-term impacts and potential challenges of SSIBE implementation.